Decomposition Analysis of CO2 Emissions from Electricity Generation in Nigeria - Emodi, Nnaemeka Vincent; Boo, Kyung-Jin (International Journal of Energy Economics and Policy, 2015)
This paper investigates the factors that influences the change in CO2 emissions from electricity generation in Nigeria. The Logarithmic Mean Divisia Index (LMDI) method of decomposition that was used. The main result shows that: (1) CO2 emission from electricity generation decreased by 0.59 Mt. (2) Electricity efficiency decreased CO2 emission by 2.33 Mt. (3) Electricity intensity decreased CO2 emission by 21.85 Mt (4) Economic activity increased CO2 emission by 28.27 Mt. The result from the analysis shows that CO2 emission increased in Nigeria. Electricity efficiency and intensity contributed to the reduction of CO2 emission while economic activity has contributed to the increase in CO2 emission in Nigeria. Since economic activities can not be reduced without affecting the economic performance of Nigeria, energy efficiency improvement would be an important option to reduce CO2 emissions. Keywords: Nigeria, decomposition analysis, CO2 emission from electricity generation, electricity efficiency, electricity intensity JEL Classifications: C01; Q41; Q43